Developing a Framework for Inclusive Education in Schools for the Visually Impaired: Advancing SDG 4 on Quality Education - Abdillah Rofiq, Aris; Agung Budi, Sardjono (INTI International University, 2025)
According to data from the Indonesian Ministry of Health, around 1.5% of the total population, or about 4 million people, are visually impaired. This contrasts with the limited availability of educational facilities in Indonesia that are specifically designed with sensory environments for the blind. Most Special Schools (SLB) still combine different types of disabilities in one learning environment, which creates serious challenges since the spatial orientation and learning needs of blind students are unique. This study is based on the limitations of national regulations, namely the Regulation of the Ministry of Public Works and Housing (PUPR) No. 14 of 2017, the Regulation of the Ministry of Education No. 33 of 2008, and the Inclusive Education Guidelines (2022). These regulations only emphasize general physical accessibility and do not accommodate a multisensory approach. The research develops an architectural design framework using the Systematic Literature Review (SLR) method and comparative analysis of three government regulations, as well as precedent studies of blind schools in India, Mexico, and Thailand. The findings reveal a significant gap: the precedent studies apply innovative strategies in sensory-based spatial design. The proposed framework integrates four sensory modalities haptic, auditory, olfactory, and visual to optimize five key aspects: navigation, safety, comfort, education, and stimulation. This framework offers practical guidance for architects while also laying the groundwork for future policy improvements to foster genuinely inclusive learning environments